2023
DOI: 10.1038/s41598-023-27994-6
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing macular edema in retinitis pigmentosa through a combined structural and microvascular optical coherence tomography investigation

Abstract: The aim of the study was to characterize macular edema (ME) in retinitis pigmentosa (RP) by means of quantitative optical coherence tomography (OCT)-based imaging. The study was designed as observational, prospective case series, with 1-year follow-up. All RP patients underwent complete ophthalmologic assessment, including structural OCT, OCT angiography, and microperimetry (MP). The primary outcome was the characterization through quantitative OCT-based imaging of RP eyes complicated by ME. A total of 68 RP p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…Further support for our results comes from the hypothesis that the pattern of BCVA in patients with RP-related CME is influenced more by outer layer integrity than by CMT. [21][22][23] In this regard, chronic CME may play a role in disrupting the photoreceptor layers, thus limiting changes in functional metrics. Interestingly, eyes treated with topical CAI showed significant and progressive improvement at all time points except month 1: less fluctuation in CMT and reduced spikes with respect to IVDI treatment suggest a better effect on BCVA.…”
Section: Discussionmentioning
confidence: 99%
“…Further support for our results comes from the hypothesis that the pattern of BCVA in patients with RP-related CME is influenced more by outer layer integrity than by CMT. [21][22][23] In this regard, chronic CME may play a role in disrupting the photoreceptor layers, thus limiting changes in functional metrics. Interestingly, eyes treated with topical CAI showed significant and progressive improvement at all time points except month 1: less fluctuation in CMT and reduced spikes with respect to IVDI treatment suggest a better effect on BCVA.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, thinning of the choroidal vessels also contributes to histopathological changes in patients with RP. OCT imaging could reveal characteristic morphological changes in RP, such as thinning of the retinal layer and choroid [ 21 ]. Previous animal studies have indicated that intraperitoneal injection of HRW could improve retinal morphology in an RP animal model induced by N-methyl-N-nitrosourea (MNU), as evidenced by the examinations of the retinal sections and OCT scanning [ 22 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…The mean follow-up ranged between 2 months and 36 months [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31]. Overall, significant reductions in both the superficial capillary plexus (SCP) and deep capillary plexus (DCP) were observed in all the affected patients of the evaluated cohorts over time [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31]. In addition, all the studies that explored the involvement of choriocapillaris (CC) demonstrated its significant impairment in RP patients [12,[15][16][17][21][22][23]25,…”
Section: Oct-a In Retinitis Pigmentosamentioning
confidence: 99%
“…Overall, significant reductions in both the superficial capillary plexus (SCP) and deep capillary plexus (DCP) were observed in all the affected patients of the evaluated cohorts over time [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31]. In addition, all the studies that explored the involvement of choriocapillaris (CC) demonstrated its significant impairment in RP patients [12,[15][16][17][21][22][23]25,30,31]. Several authors focused on the variation of the foveal avascular zone (FAZ) area in RP patients, two-thirds of which described an increased avascular area [12,15,19,20,26,31], while the remaining third demonstrated its significant reduction [16,17,29].…”
Section: Oct-a In Retinitis Pigmentosamentioning
confidence: 99%
See 1 more Smart Citation